Penerapan Threpahy Slimber Ice untuk Menurunkan Rasa Haus dalam Asuhan Keperawatan Hipervolemia di Ruang Rosella RSUD Kardinah Kota Tegal - Aiyeni Aiyeni; Nonok Karlina; Muadi Muadi (JURNAL ILMIAH KESEHATAN MASYARAKAT DAN SOSIAL, 2026)
Chronic Kidney Disease is a condition when kidney function begins to decline gradually. Chronic kidney failure disease called kidney damage can be tissue abnormalities, blood composition, and urine or kidney imaging tests, experienced for more than three months. This scientific paper aims to analyze nursing care with the application of slimber ice therapy  to chronic kidney disease  clients with hypervolemia nursing problems. The method applied in the preparation of this scientific paper is the case study method. The subject of this scientific paper is involving 1 client with a case of CKD and having hypervolemia nursing problems who are undergoing treatment in the Rosella Room of Kardinah Hospital, Tegal City. Data collection uses interview, observation, and physical examination techniques. The nursing care process for the client was carried out for 3 days, and the results of the assessment were obtained, namely edema in both lower extremities. The intervention provided is in the form of fluid restriction with the application  of slimber ice  therapy to reduce thirst which is implemented for 3 days, with slimber ice therapy  for 5-10 minutes during dialysis sessions can reduce thirst and can moisturize the esophagus so as to reduce thirst and minimize fluid input in the body. Based on the results of the evaluation, it was found that the application  of slimber ice therapy  on the first to third day was able to reduce thirst in CKD patients undergoing hemodialysis.